An introduction to computational fluid mechanics by example - Biringen, Sedat; Chow, Chuen-Yen, 1932-; Wiley InterScience (Online service) (Hoboken, N.J. : Wiley, 2011)
"The proposed book will be a revision and update of the textbook entitled: "An Introduction to Computational Fluid Mechanics" by C.Y. Chow which was originally published in 1979. The original edition was written for senior undergraduate and first-year graduate students as well as professional engineers and researchers in the mechanical and aerospace industries. In the decades that have passed since this first edition was published the field of computational fluid dynamics has seen a number of changes in both the sophistication of the algorithms used but also advances in the computer hardware and software available. The proposed revision will incorporate the latest algorithms in the solution techniques and will support this by using numerous examples of applications to a broader range of industries from the original mechanical and aerospace disciplines to now include civil and biosciences. The computer programs will be updated and will include both Fortran 77 and MATLAB. The core of the text will also be expanded to include more up-to-date solution methods for the Navier-Stokes equations, including fractional step time-advancement, and pseudo-spectral methods. A solutions manual will be made available as well."--
"This book builds on the original classic textbook entitled: "An Introduction to Computational Fluid Mechanics" by C.Y. Chow which was originally published in 1979. The original edition was written for senior undergraduate and first-year graduate students as well as professional engineers and researchers in the mechanical and aerospace industries. In the decades that have passed since this book was published the field of computational fluid dynamics has seen a number of changes in both the sophistication of the algorithms used but also advances in the computer hardware and software available"--
Frontmatter -- Flow Topics Governed by Ordinary Differential Equations: Initial-Value Problems -- Inviscid Fluid Flows -- Viscous Fluid Flows -- Numerical Solution of the Incompressible Navier-Stokes Equation -- Bibliography -- Index.
Includes bibliographical references (pages 298-302) index.
Print version record.
Keywords: Fluid mechanics; Fluid mechanics -- Data processing; Fluid mechanics -- Data processing; Fluid mechanics; SCIENCE -- Mechanics -- General; Fluid mechanics; Fluid mechanics -- Data processing; Electronic books; Electronic books